Academic problems facing a sample of female students of theoretical colleges at King Abdulaziz University from their point of view (Journal of the College of Education for Women, 2024)
This study aims to identify the most prominent academic problems facing female students in the theoretical faculties at King Abdul Aziz University and to know their results and ways to address them. The descriptive method was used, and the study sample consisted of (277) female theoretical college students from the following levels (third - fourth - fifth - sixth) at King Abdulaziz University, and they were randomly chosen. A list of academic problems questionnaire for university students prepared by Barzawi (2017) was applied. The results of the study showed that the problems related to the student's relationship with professors rank first, followed by studying materials, exams, academic advising, then the student's relationship with the university's surroundings, and lastly studying skills. The importance of this study and its findings is evident in helping decision makers in the academic field to assist facilitating the educational process for female students by increasing their awareness of these problems and ways to overcome them.